Prevalence and risk factors of nonalcoholic fatty liver disease in HIV-monoinfection. (17th July 2017) - Maurice, James B.; Patel, Amee; Scott, Alasdair J.; Patel, Krish; Thursz, Mark; Lemoine, Maud
Abstract : Objective: To identify the prevalence and risk factors of nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH) and fibrosis in HIV-monoinfected patients. Design: Systematic review and meta-analysis. Methods: We searched Medline and Embase and included studies that enrolled HIV-monoinfected patients with NAFLD defined by imaging and/or liver histology. Data on prevalence and risk factors for NAFLD, NASH and fibrosis were collected for meta-analysis using random effects models. Results: Ten studies were included from the United States of America ( n = 4), Canada ( n = 1), France ( n = 2), Italy ( n = 1), Japan ( n = 1) and China ( n = 1). The prevalence of NAFLD (Imaging studies), NASH and fibrosis (biopsied populations) were 35% [95% confidence interval (CI) 29–42], 42% (95% CI 22–64) and 22% (95% CI 13–34), respectively. Meta-analysis of risk factors showed that high BMI, waist circumference, type 2 diabetes, hypertension, triglycerides and high CD4 + cell count were associated with NAFLD, whereas HIV viral load, duration of HIV infection, duration of antiretroviral therapy and CD4 + cell count nadir were not. Patients with high BMI [mean difference (MD) 1.38, 95% CI 0.04–2.71 P = 0.04], fasting glucose (MD 0.80, 95% CI 0.47–1.13 P < 0.00001) and AST level (MD 13.00, 95% CI 4.34–21.65 P = 0.003) were at increased risk of significant liver fibrosis. Conclusion: NAFLD is frequently observed in HIV-monoinfected patients, and NASH is a common cause of unexplained abnormal liver function in patients selected for liver biopsy. Metabolic disorders are key risk factors independently of HIV parameters. Future trials on pharmacological interventions in NASH with fibrosis should include patients with HIV. Abstract : Supplemental Digital Content is available in the text